Liquid phase densification of Al-4.5 wt.% Cu powder reinforced with 5 wt.% Saffil short fibers during hot pressing - Moreno, M. F. (2013)
The Alumix 13 (wt.%) (Al–4.5 Cu 0.5 Mg 0.2 Si) powder with and without 5 wt.% Saffil short fibers specimens were hot pressed in the range 580–620 °C. The densification during pressure increase was fitted using the Konopicky model and an agreement with the associated linear plot P vs. ln(1/(1 − D) was found for both materials, where P is applied pressure and D is the relative density of the porous material. The transient liquid phase formed from the elemental Al and Cu powder particles above the eutectic temperature of 548 °C at low hot pressing pressures, allows to increase the densification due to the reduction in the yield stress of the porous material. The active liquid flow enhanced the deformation between Al particles in the beginning of the pressure ramp. For higher pressures, a sudden break to a higher slope in Konopicky plot was found. This hardening behavior was detected from 610 °C for pure Alumix 13 and it was systematically developed at 580, 600, 610 and 620 °C for the composites, and it can be assigned to diffusion of Cu into the Al grains. During the constant pressure stage the densification was well fitted using the Power Law Creep model with exponents of n = 1 and n = 2, which are related to Newtonian viscous flow and superplastic deformation, respectively. Besides, final hot pressed composites samples retained an important quantity of solidified liquid phase located in between the Saffil fibers agglomerates.